Rancang Bangun Sistem Lighter Lamp Berbasis Mikrokontroler Arduino Uno - Lighter Jhosua Simanjuntak; Dedy Hartama; Ika Okta Kirana (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2021)
Along with the times it can be said that smartphones are one of the primary needs. Another primary need is electricity, the need for electricity is very large but sometimes people use it lavishly. The form of this waste is that sometimes people are lazy or forget to turn off electrical devices such as lights when they have done something. On the other hand, the development of technological developments continues to be developed to facilitate all community activities, one of the developing technology fields is Arduino Uno technology. The application of Arduino Uno technology is to control room electricity using a smartphone, where this system can control the room's electrical devices